Faktor-Faktor Information Adoption Model terhadap Purchase Intention: Studi pada Media Sosial Tiktok Azarine Cosmetic - Avifah; Saputri, Marheni Eka (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The development of the cosmetic industry in Indonesia has experienced rapid growth. This development has caused cosmetic brands in Indonesia to use marketing strategies to increase purchase intention. One of the ways used by cosmetic brands in Indonesia to increase their purchase intention is by utilizing social media as a marketing strategy. This study aims to determine and analyze the factors of information adoption model on purchase intention (study on TikTok social media Azarine Cosmetic). The method used in this study is quantitative with a causal descriptive form. This study uses non-probability sampling type purposive sampling as a sampling technique. Therefore, as many as 410 respondents identified as consumers of Azarine Cosmetics at Shopee were set as samples in this study. The results of the analysis found that the variable factors of the information adoption model have a positive and significant influence on purchase intention. The conclusion of this study, Azarine Cosmetic should pay attention to the use of information adoption models provided through content on TikTok social media if they want to continue to increase consumer purchase intention.